KISAH AṢḤᾹB AL-JANNAH DALAM AL-QUR’AN (Q.S AL-QALAM AYAT 17-33) - Alfattiah Aldin (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2022)
The story discussed in this study is the story of the garden owner in the Qur'an, this story is contained in Surah al-Qalam verses 17-33 about the garden owner who does not want to share with the poor. This resulted in, Allah swt destroy the garden. The formulation of the problem in this study is how 'ibrah is from the story of the garden owner and how is the relevance of the story of the garden owner in Surah al-Qalam verses 17-33 in the present context. The method used is the method (taḥlīlī) and descriptive-analysis. From the results of this study, the author concludes that, 'ibrah and the relevance of the story to the present context are (1) Arrogant people must be harmed. (2) Greedy and miserly people do various tricks to get as much wealth as possible even though it is at the expense of or oppressing others. (3) People who are arrogant and do deceit will surely be disappointed and regretful. (4) The importance of advising each other in dealing with various problems in life. (5) As well as realizing mistakes, immediately repent and expect His grace to give peace in life.